2020
DOI: 10.1590/1413-7054202044005220
|View full text |Cite
|
Sign up to set email alerts
|

Allometric models for estimating Moringa oleifera leaflets area

Abstract: ABSTRACT Moringa oleifera is a species of great economic, social and environmental importance, being employed for multiple purposes. Thus, the objective of this study was to fit regression models for estimating leaflets area as non-destructive method from linear measurements of leaflets of M. oleifera seedlings. The study was carried out at the Center for Agrarian and Environmental Sciences of the Paraíba State University. Three hundred leaflets of M. oleifera were collected and measured to determine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
2
8
0
4
Order By: Relevance
“…The conventional method of estimating geometric leaf properties, especially the leaf area, uses allometric relationships. These equations have been successfully applied to various plants, such as Gossypium herbaceum L., Fritillaria przewalskii Maxim., Erythroxylum pauferrense T. Plowman, Moringa oleifera Lam., and tree species (Barbosa, Santos, & Albuquerque, 2020;Forrester et al, 2017;Johnson, 1967;Ma, Xu, Chen, Guo, & Wu, 2020;Macário et al, 2020). In this research, we used digital image processing to measure the geometric properties of leaves in wheat and triticale.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional method of estimating geometric leaf properties, especially the leaf area, uses allometric relationships. These equations have been successfully applied to various plants, such as Gossypium herbaceum L., Fritillaria przewalskii Maxim., Erythroxylum pauferrense T. Plowman, Moringa oleifera Lam., and tree species (Barbosa, Santos, & Albuquerque, 2020;Forrester et al, 2017;Johnson, 1967;Ma, Xu, Chen, Guo, & Wu, 2020;Macário et al, 2020). In this research, we used digital image processing to measure the geometric properties of leaves in wheat and triticale.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the best equations to estimate the LA of peanut cultivars were those that used LW, compared to equations that used only one leaflet dimension (L or W), with the best criteria and adjustments of the models used (Guimarães et al 2019, Macário et al 2020, Goergen et al 2021, except for the exponential model, in which the best equations were those that used L of the leaflets (Ribeiro et al 2020).…”
Section: Discussionmentioning
confidence: 81%
“…In this scenario, Moringa oleifera Lamarck, a species of the family Moringaceae and native to India and Pakistan [ 3 ], could be one such alternative for cultivation given its various food, medicinal, industrial, environmental, and social purposes, and as an abundant source of essential amino acids, macronutrients, and micronutrients. This species also shows outstanding anti-fungal, analgesic, anti-inflammatory, anti-oxidant, anti-diabetic, anti-tumoral, and anti-bacterial properties, with high seed oil contents [ 4 , 5 , 6 , 7 , 8 ]. Furthermore, the species can also be used to purify water, generate income, and improve the quality of life of producers around the world [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This species also shows outstanding anti-fungal, analgesic, anti-inflammatory, anti-oxidant, anti-diabetic, anti-tumoral, and anti-bacterial properties, with high seed oil contents [ 4 , 5 , 6 , 7 , 8 ]. Furthermore, the species can also be used to purify water, generate income, and improve the quality of life of producers around the world [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%